WEB COMPUTER TOOL BASED ON GENETIC ALGORITHMS FOR ROUTING VEHICLES - Alessandro Rocha Santos, Renato; Jefferson de Araujo Lima, Stanley; Alves de Araújo, Sidnei (LINKSCIENCEPLACE, 2026)
Over the last decades the Vehicle Routing Problem (VRP) has been subject of several researches, mainly due to the difficulties found in its optimization as well as its aplicability in real-world situations. In the scientific literature there are several proposed solutions for the PRV using different optimization techniques. However, such solutions are rarely transformed into software tools that can be used by end users, for example, microenterprises. Thus, the focus of the present work was to develop a Web computational tool for vehicle routing, called SGRV Sistema de Gestão de Roteamento de Veículos, which uses Google Maps resources and aims to meet the needs of microenterprises. All steps of this research were conducted based on Design Science Research methodology. The SGRV was qualitatively evaluated by four microenterprises from different branches, that used it for a certain period and, at the end, answered six opened questions through semi-structured interviews. The experiences of these microenterprises were transcribed and the obtained data reveal the effectiveness of the SGRV in the management of their tasks related to the orders and deliveries of products.